Czech Republic: Critical Legal Analysis on Dogmatic and Current Issues of Labor Law - Štefko, Martin (Fundamentals of Labor Law in Central Europe, 2022)
The purpose of this chapter is to analyze Czech labor law. The first part describes its position in the Czech legal order, the parts of which it is composed, and the ‘big’ legislative compromise derived by the Czech legislature, when the more flexible approach was taken after the millennium. The second part identifies two key legal issues that need to be addressed in relation to Czech labor law in the post-COVID period. The Czech political representatives have not yet been able to agree on basic conceptual measures to protect society, the country, or the economy. The indebtedness of the country and individuals is rising, as is mortality and the domestic violence rate. The Czech society is split, both ideologically and as far as the discourse between generations is concerned. Some people want to protect themselves, while others want to live even at the expense of those facing a threat. Keywords: COVID-19 testing, collective agreements, voluntary fire fighters, occupational injuries